Exploring the role of blockchain technology in medical education: Future opportunities and challenges - Hossein Moradimokhles; Maryam Pourjamshidi; Omid Mozafari (Zanjan University of Medical Sciences and Health Services, 2024)
Background & Objective: Today, blockchain technology presents a new framework that can help address some challenges facing health and medical education. Accordingly, there is a growing interest in using this important technology, especially among medical educators. Looking towards the future of educational technology and considering the end of the COVID-19 pandemic, medical education experts are expected to accept blockchain technology widely. This study aims to investigate all aspects related to the application of blockchain in medical education. Material & Methods: The study was conducted through a PRISMA systematic review of 10 databases, namely Scopus, Web of Science, Eric, Wiley Online Library, ProQuest, Springer, Noormags, Magiran, and Irandoc, in December 2022, and was updated in February 2023. By utilizing the strategies of this systematic review, a total of 980 related articles were identified, of which 187 were selected. After screening and criteria were applied, 18 relevant articles were selected to complete the research. Results: The results show that the application of blockchain technology in medical education has the most significant impact in the two sectors of education and healthcare. In health and treatment, blockchain technology plays a crucial role in registering patients' treatment records, storing treatment information, and ensuring the security and durability of information. In medical education, blockchain technology is utilized to issue educational certificates, enhance credibility, offer cloud storage space, and enhance the quality of teaching and learning. The trend in research methods is shifting towards mixed methods. Conclusion: According to this study, blockchain technology in medical education creates suitable capacities for learners and teachers through a systemic approach and collective wisdom. Despite the positive aspects and efforts to address the challenges, the field of medical education is still experiencing an exponential trend in the use of technology. We expect more research and the integration of blockchain technology in medical education in the short term.